Avaliação da degradação do corante azul de metileno por diferentes processos oxidativos avançados - Rosa, Ricardo Henrique Santin da (2016)
Blue methylene cationic dye have a broad use as coloring in some industries, especially in textile industry, and also in the universities research laboratories. The treatment of solutions containing dyes often are complex and expensive, because of that, in some cases, improper disposal of these solutions are made. For this reason it is extremely important to realize new studies for treatments of colored solutions that are cheaper, fast and efficient. This work was focused on the evaluation of the application from different advanced oxidation processes for degradation of a solution containing the dye blue methylene catiônicoThe Fenton methods were applied and photo-Fenton containing combinations of different amounts of reagents, besides of UV irradiation in the second method, and we also used the photolytic method which used only the UV irradiation by a mercury vapor lamp to degrade the dye. The Fenton methods and photo-Fenton showed high efficiency, 92.34% and 96.40%, respectively, with small amounts of reagents and extremely small time for degradation .The photolytic method showed low efficiency of 24.18%, even with lot amount of time, 13 hours in reaction. Among the three techniques the one that was more efficient was the photo-Fenton, using less reagents, and obtaining high efficiency in a short reaction time.